Energy consumption study of channel access modes and modulation schemes of the 2.4 GHz narrowband IEEE 802.15.6 - Marwa Boumaiz; Mohammed El Ghazi; Mohammed Fattah; Anas Bouayad; Moulhime El Bekkali (Indonesian Journal of Electrical Engineering and Computer Science, 2021)
Energy efficiency is an important challenge for wireless body area networks. Therefore, choosing the channel access modes and modulation schemes that guarantee lower energy consumption is necessary to increase the network lifetime, especially in wireless body area network (WBAN) medical applications. The purpose of this paper is to analyze the network energy consumption in on-body medical applications (which are classified as low data rate, medium data rate, and high data rate applications) for two channel access mechanisms: random and scheduled access modes, and two modulation schemes: differential quadrature phase shift keying (DQPSK) and differential binary phase shift keying (DBPSK), which are supported by the 2.4 GHz band of the Institute of Electrical and Electronics Engineers (IEEE) 802.15.6 standard. The considered on-body area network (BAN) of the study supports two communication scenarios: the line-of-sight transmission and the non-line-of-sight communications, referenced as CM3A and CM3B path loss models respectively. Simulation results have demonstrated that the scheduled access mode based on time-division multiple access (TDMA), and DQPSK are the optimal choices to be made at the media access control (MAC) and physical layer levels respectively, in terms of energy efficiency, in low, medium, and high data rate on-body WBAN applications.